Binder composition for nonaqueous secondary battery electrode, slurry composition for nonaqueous secondary battery electrode, electrode for nonaqueous secondary battery, and nonaqueous secondary battery

CN123023148APending Publication Date: 2026-10-30ZEON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580022079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-25
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0065]根据本发明,能够提供一种能够赋予非水系二次电池用电极优异的剥离强度的非水系二次电池电极用黏结剂组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123023148A_ABST
    Figure CN123023148A_ABST
Patent Text Reader

Abstract

The present invention aims to provide a binder composition for a nonaqueous secondary battery electrode capable of imparting an electrode for a nonaqueous secondary battery with excellent peel strength. The present invention is a binder composition for a nonaqueous secondary battery electrode comprising a particulate polymer, wherein at least one combination of a transverse relaxation time T2 obtained by CPMG method measurement of pulsed NMR at one point in a range of pH 3.0 or higher and 4.5 or lower and a transverse relaxation time T2 obtained by CPMG method measurement of pulsed NMR at one point in a range of pH 6.5 or higher and 8.0 or lower satisfies the following relation (1). 2A at least one combination of a transverse relaxation time T2 obtained by CPMG method measurement of pulsed NMR at one point in a range of pH 3.0 or higher and 4.5 or lower and a transverse relaxation time T2 obtained by CPMG method measurement of pulsed NMR at one point in a range of pH 6.5 or higher and 8.0 or lower satisfies the following relation (1). 2B the following relation (1):
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to binder compositions for electrodes of non-aqueous secondary batteries, slurry compositions for electrodes of non-aqueous secondary batteries, electrodes for non-aqueous secondary batteries, and non-aqueous secondary batteries. Background Technology

[0002] Non-aqueous secondary batteries, such as lithium-ion batteries (hereinafter sometimes simply referred to as "secondary batteries"), are characterized by their small size, light weight, high energy density, and ability to be repeatedly charged and discharged, making them suitable for a wide range of applications. Therefore, in recent years, research has been conducted on improving battery components, including batteries, with the aim of further enhancing the performance of non-aqueous secondary batteries.

[0003] Here, the electrode used in secondary batteries such as lithium-ion secondary batteries typically has a current collector and an electrode composite material layer (positive electrode composite material layer or negative electrode composite material layer) formed on the current collector. Moreover, the electrode composite material layer is formed, for example, by coating a slurry composition containing an electrode active material and a binder composition containing a binder onto the current collector and drying the coated slurry composition.

[0004] A binder composition for use in slurry compositions is being developed to improve the performance of secondary batteries.

[0005] For example, Patent Document 1 discloses an adhesive composition that can form an electrode for a non-aqueous secondary battery with excellent peel strength. The composition comprises a particulate polymer, wherein the proportions of aromatic vinyl monomer units, aliphatic conjugated diene monomer units, and carboxyl-containing monomer units in the particulate polymer are within a specified range, and the ratio (Da / Db) of the average particle size Da of the particulate polymer as determined by dynamic light scattering to the volume average particle size Db of the particulate polymer as determined by laser diffraction scattering is within a specified range, and the volume average particle size Db of the particulate polymer is within a specified range.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent document 1: International Publication No. 2023 / 008582. Summary of the Invention

[0009] The problem the invention aims to solve

[0010] Here, regarding the adhesive composition, there is a need for further improvement in imparting excellent peel strength to the electrode.

[0011] Therefore, the object of the present invention is to provide an adhesive composition for a non-aqueous secondary battery electrode that can impart excellent peel strength to the electrode for a non-aqueous secondary battery.

[0012] Furthermore, the present invention aims to provide a slurry composition for a non-aqueous secondary battery electrode that can impart excellent peel strength to the electrode of a non-aqueous secondary battery.

[0013] Furthermore, the present invention aims to provide an electrode for a non-aqueous secondary battery with excellent peel strength.

[0014] Furthermore, the purpose of this invention is to provide a high-performance non-aqueous secondary battery.

[0015] Solution for solving the problem

[0016] To address the aforementioned problems, the inventors conducted in-depth research. Furthermore, the inventors have discovered that, in the case of a binder composition for a non-aqueous secondary battery electrode containing a particulate polymer, the transverse relaxation time T obtained by pulsed NMR CPMG measurement at a single point within a pH range of 3.0 to 4.5 for the particulate polymer... 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B If at least one combination of the given conditions satisfies the specified relationship, the above-mentioned problem can be solved, thereby completing the present invention.

[0017] That is, the present invention aims to advantageously solve the above-mentioned problems. [1] The present invention is a binder composition for a non-aqueous secondary battery electrode, which comprises a particulate polymer, wherein the transverse relaxation time T obtained by pulse NMR CPMG method determination of the particulate polymer at a point in the range of pH 3.0 and 4.5 is obtained. 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B At least one combination of them satisfies the following relationship (1):

[0018] .

[0019] The aforementioned adhesive composition for non-aqueous secondary battery electrodes (hereinafter, sometimes simply referred to as "adhesive composition") can impart excellent peel strength to non-aqueous secondary battery electrodes (hereinafter, sometimes simply referred to as "electrodes").

[0020] In this specification, the transverse relaxation time T of the particulate polymer is... 2A It can usually be determined using the following methods.

[0021] <<Pulse NMR Measurement>>

[0022] First, the binder composition of the present invention was adjusted to a solid content concentration of 29.0% by mass or more and 31.0% by mass or less, and a pH of 3.0 or more and 4.5 or less. The adjusted binder composition was then introduced into a glass sample tube with a diameter of 10 mm. The sample tube was placed in a pulsed NMR apparatus (such as a Bruker MQ20) and measured at 30°C using the CPMG method (Carr-Purcell-Meiboom-Gill method) under the following conditions to obtain the following results. 1 The free induction decay curve of H's transverse relaxation.

[0023] -Conditions for CPMG method-

[0024] · 1 H-resonance frequency: 20MHz;

[0025] • Total number of times: 64;

[0026] • Repeat time: 2 seconds;

[0027] • Number of measurement points: 1000.

[0028] <<Calculation of Lateral Relaxation Time T2>>

[0029] The transverse relaxation time T2 was obtained by fitting the free induction decay curve y(t) obtained above with an exponential function. Additionally, the analysis software "TDNMR-A" manufactured by Bruker was used, and the function was fitted with an exponential function according to the product manual. Furthermore, the fitting was performed using the following equation (2).

[0030]

[0031] In equation (2), A represents the signal strength at t=0, T2 represents the transverse relaxation time, and t represents time. Using the CPMG method described above, the transverse relaxation time T2 is measured three times, and its average value is calculated. This average value is taken as the transverse relaxation time T. 2A Additionally, for example, the transverse relaxation time T of particulate polymers 2A The measurement can be performed according to the method described in the examples.

[0032] In this specification, the transverse relaxation time T of the particulate polymer is... 2B It can usually be determined using the following methods.

[0033] <<Pulse NMR Measurement>>

[0034] First, the binder composition of the present invention was adjusted to a solid content concentration of 29.0% by mass or more and 31.0% by mass or less, and a pH of 6.5 or more and 8.0 or less. The adjusted binder composition was then introduced into a glass sample tube with a diameter of 10 mm. The sample tube was placed in a pulsed NMR apparatus (such as a Bruker MQ20) and measured at 30°C using the CPMG method (Carr-Purcell-Meiboom-Gill method) under the following conditions, yielding the following results. 1 The free induction decay curve of H's transverse relaxation.

[0035] -Conditions for CPMG method-

[0036] · 1 H-resonance frequency: 20MHz;

[0037] • Total number of times: 64;

[0038] • Repeat time: 2 seconds;

[0039] • Number of measurement points: 1000.

[0040] <<Calculation of Lateral Relaxation Time T2>>

[0041] The transverse relaxation time T2 was obtained by fitting the free induction decay curve y(t) obtained above with an exponential function. Additionally, the analysis software "TDNMR-A" manufactured by Bruker was used, and the function was fitted with an exponential function according to the product manual. Furthermore, the fitting was performed using the following equation (2).

[0042]

[0043] In equation (2), A represents the signal strength at t=0, T2 represents the transverse relaxation time, and t represents time. Using the CPMG method described above, the transverse relaxation time T2 is measured three times, and its average value is calculated. This average value is taken as the transverse relaxation time T. 2B Additionally, for example, the transverse relaxation time T of particulate polymers 2B The measurement can be performed according to the method described in the examples.

[0044] [2] In the above-mentioned [1] non-aqueous secondary battery electrode binder composition, the above-mentioned transverse relaxation time T is preferred. 2B It is between 10 msec and 1500 msec.

[0045] If the lateral relaxation time T 2B Within the aforementioned range, peel strength can be improved.

[0046] [3] In the binder composition for non-aqueous secondary battery electrodes of [1] or [2] above, it is preferable that the particulate polymer contains aromatic vinyl monomer units.

[0047] If the particulate polymer contains aromatic vinyl monomer units, the internal resistance of the resulting secondary battery can be reduced.

[0048] [4] In the binder composition for non-aqueous secondary battery electrodes of any one of [1] to [3] above, it is preferable that the volume average particle size of the particulate polymer is 100 nm or more and 300 nm or less.

[0049] If the volume average particle size of the particulate polymer is above the aforementioned lower limit, the internal resistance of the resulting secondary battery can be reduced. Furthermore, the electrolyte injection properties of the electrode composite layer can be improved.

[0050] On the other hand, if the volume average particle size of the particulate polymer is below the above-mentioned upper limit, the adhesiveness of the binder composition can be well maintained.

[0051] In this specification, the volume average particle size refers to the particle size (D50) at which the cumulative volume calculated from the smallest particle size side in the particle size distribution reaches 50%, and can be measured according to the method described in the embodiments of this specification.

[0052] [5] In the binder composition for non-aqueous secondary battery electrodes of any one of [1] to [4] above, the insoluble component of the particulate polymer in tetrahydrofuran is preferably 70% by mass or more.

[0053] If the percentage of the insoluble component of the particulate polymer in tetrahydrofuran is above the lower limit mentioned above, the adhesive properties of the binder composition can be well maintained.

[0054] In this specification, the percentage of particulate polymers in tetrahydrofuran (THF) (hereinafter, sometimes referred to as "THF insoluble percentage") can generally be determined by the following method.

[0055] First, the adhesive composition of the present invention is dried in an environment with 50% humidity and a temperature of 23-25°C to form a film with a thickness of 1 ± 0.3 mm. Next, the film is dried in a vacuum dryer at a temperature of 60°C for 10 hours. After that, the dried film is cut into 3-5 mm squares and weighed precisely about 1 g. Here, the mass of the film obtained by cutting is set as w0. The obtained film is immersed in 50 g of tetrahydrofuran (THF) for 24 hours. After that, the film removed from THF is vacuum dried at a temperature of 105°C for 3 hours, and the mass of the insoluble component w1 is measured. Then, the THF insoluble component percentage is calculated using the following formula (3).

[0056]

[0057] Additionally, for example, the percentage of THF-insoluble components in the particulate polymer can be determined according to the method described in the examples.

[0058] Furthermore, with the aim of advantageously solving the above-mentioned problems, [6] the present invention is a slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material and a binder composition for a non-aqueous secondary battery electrode of any one of [1] to [5] above.

[0059] The aforementioned non-aqueous secondary battery electrode slurry composition (hereinafter, sometimes simply referred to as "slurry composition") can impart excellent peel strength to the electrode.

[0060] Furthermore, with the aim of advantageously solving the above-mentioned problems, [7] the present invention is an electrode for a non-aqueous secondary battery having an electrode composite material layer formed using the above-described [6] non-aqueous secondary battery electrode slurry composition.

[0061] The aforementioned electrodes exhibit excellent peel strength.

[0062] Furthermore, with the aim of advantageously solving the above-mentioned problems, [8] the present invention is a non-aqueous secondary battery comprising a positive electrode, a negative electrode, a spacer and an electrolyte, wherein at least one of the positive electrode and the negative electrode is an electrode for a non-aqueous secondary battery as described in [7].

[0063] The aforementioned secondary batteries exhibit excellent performance.

[0064] Invention Effects

[0065] According to the present invention, it is possible to provide an adhesive composition for a non-aqueous secondary battery electrode that can impart excellent peel strength to the electrode for a non-aqueous secondary battery.

[0066] Furthermore, according to the present invention, a slurry composition for a non-aqueous secondary battery electrode can be provided, which can impart excellent peel strength to the electrode for a non-aqueous secondary battery.

[0067] Furthermore, according to the present invention, an electrode for a non-aqueous secondary battery with excellent peel strength can be provided.

[0068] Furthermore, according to the present invention, a non-aqueous secondary battery having electrodes for a non-aqueous secondary battery with excellent performance can be provided. Detailed Implementation

[0069] The embodiments of the present invention will now be described in detail.

[0070] Here, the binder composition of the present invention can be used to prepare the slurry composition of the present invention. Furthermore, the slurry composition prepared using the binder composition of the present invention can be used in the manufacture of electrodes for secondary batteries such as lithium-ion secondary batteries. Moreover, the secondary battery of the present invention is characterized by the use of the electrode of the present invention formed using the slurry composition of the present invention.

[0071] Furthermore, the binder composition, slurry composition, and electrode of the present invention are preferably used as negative electrodes, and the secondary battery of the present invention is preferably a secondary battery in which the electrode of the present invention is used as a negative electrode.

[0072] (Binder composition for non-aqueous secondary battery electrodes)

[0073] The binder composition for non-aqueous secondary battery electrodes of the present invention comprises a particulate polymer and may also typically include a solvent. Furthermore, the transverse relaxation time T obtained by pulsed NMR CPMG determination of the particulate polymer at a single point within a pH range of 3.0 to 4.5 is... 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B At least one combination of them satisfies the following relationship (1):

[0074] .

[0075] Furthermore, the binder composition of the present invention typically does not contain electrode active materials.

[0076] <Particulate Polymers>

[0077] Particulate polymers function as adhesives and, in electrode composite material layers formed using slurry compositions containing adhesive compositions, can prevent components such as electrode active substances from detaching from the electrode composite material layer.

[0078] Here, the particulate polymer is preferably a non-water-soluble particle. Furthermore, in this specification, "non-water-soluble" polymer particles mean that when 0.5g of the polymer is dissolved in 100g of water at 25°C, the insoluble component is 90% by mass or more.

[0079] The transverse relaxation time T of the particulate polymer contained in the binder composition of the present invention was determined by pulse NMR CPMG at a single point within a pH range of 3.0 to 4.5. 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B At least one combination of them satisfies the following relationship (1):

[0080] .

[0081] Using the above-mentioned particulate polymer in the binder composition can impart excellent peel strength to the electrode. The reasoning is that the transverse relaxation time T2 obtained during pulsed NMR CPMG determination can serve as an indicator of the number of bound hydrogen atoms on the surface of the particulate polymer, and the transverse relaxation time T2 obtained during pulsed NMR CPMG determination at a single point within the pH range of 3.0 to 4.5... 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B At least one combination of the particulate polymers that satisfy the above equation (1) has good ionic conductivity on its surface, which results in the ability to impart excellent peel strength to the electrode.

[0082] Properties of Particulate Polymers

[0083] T of particulate polymers 2B / T 2A The value should be 1.5 or higher, preferably 2.0 or higher, more preferably 3.0 or higher, even more preferably 3.8 or higher, preferably 6.0 or lower, more preferably 5.0 or lower, even more preferably 4.5 or lower, and even more preferably 4.0 or lower.

[0084] Moreover, the T of particulate polymers 2B / T 2A Preferably, the value is 1.5 or higher and 6.0 or lower, more preferably 2.0 or higher and 5.0 or lower, even more preferably 3.0 or higher and 4.5 or lower, and even more preferably 3.8 or higher and 4.0 or lower.

[0085] If the T of the particulate polymer 2B / T 2A Above the aforementioned lower limit, the peel strength of the obtained electrode can be improved. Furthermore, the peel strength of the electrode having an electrode composite layer obtained by high-speed coating (hereinafter, sometimes referred to as "peel strength during high-speed coating") can be improved.

[0086] On the other hand, if the T of particulate polymers 2B / T 2A Below the aforementioned upper limit, the tackiness of the binder composition can be well maintained. Furthermore, the peel strength of the obtained electrode and the peel strength during high-speed coating can be improved. Consequently, the internal resistance of the obtained secondary battery can be reduced, and the cycle characteristics of the obtained secondary battery can be improved.

[0087] Lateral relaxation time T2A Preferably, the time is 0.1 msec or more, more preferably 1.0 msec or more, even more preferably 30 msec or more, preferably 5000 msec or less, more preferably 2500 msec or less, even more preferably 1000 msec or less, and even more preferably 500 msec or less.

[0088] Moreover, the lateral relaxation time T 2A Preferably, the time is 0.1 msec or more and 5000 msec or less, more preferably 1.0 msec or more and 2500 msec or less, further preferably 30 msec or more and 1000 msec or less, and even more preferably 30 msec or more and 500 msec or less.

[0089] If the lateral relaxation time T 2A Within the aforementioned range, peel strength can be improved.

[0090] Lateral relaxation time T 2B Preferably, it is 10 msec or more, more preferably 100 msec or more, more preferably 1500 msec or less, more preferably 1200 msec or less, and even more preferably 650 msec or less.

[0091] Moreover, the lateral relaxation time T 2B Preferably, the time is 10 msec or more and 1500 msec or less, more preferably 100 msec or more and 1200 msec or less, and even more preferably 100 msec or more and 650 msec or less.

[0092] If the lateral relaxation time T 2B Within the aforementioned range, peel strength can be improved.

[0093] In addition, the lateral relaxation time T 2A and lateral relaxation time T 2B It can be adjusted by, for example, the type and amount of monomers used to form particulate polymers, as well as the polymerization method and polymerization conditions.

[0094] The THF insoluble component percentage of the particulate polymer is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 93% by mass or more, and still more preferably 95% by mass or more.

[0095] If the percentage of THF-insoluble components in the particulate polymer is above the lower limit mentioned above, the adhesive properties of the binder composition can be well maintained.

[0096] In addition, the percentage of THF-insoluble components in the particulate polymer may be, for example, 99% by mass or less, or 97% by mass or less.

[0097] Furthermore, the THF insoluble component percentage of the particulate polymer is preferably 70% or more and 99% or less by mass, preferably 80% or more and 97% or less by mass, more preferably 90% or more and 97% or less by mass, even more preferably 93% or more and 97% or less by mass, and even more preferably 95% or more and 97% or less by mass.

[0098] The THF insoluble content of particulate polymers can be adjusted by, for example, the type and amount of monomers used to form particulate polymers, as well as the polymerization method and polymerization conditions.

[0099] The volume average particle size of the particulate polymer is preferably 100 nm or more, more preferably 120 nm or more, more preferably 300 nm or less, and more preferably 170 nm or less.

[0100] If the volume average particle size of the particulate polymer is above the aforementioned lower limit, the internal resistance of the resulting secondary battery can be reduced. Furthermore, the electrolyte injection properties of the electrode composite layer can be improved.

[0101] On the other hand, if the volume average particle size of the particulate polymer is below the above-mentioned upper limit, the adhesiveness of the binder composition can be well maintained.

[0102] <<Composition of Particulate Polymers>>

[0103] There are no particular limitations on particulate polymers as long as they have the physical properties specified above, but they can arbitrarily contain aromatic vinyl monomer units, aliphatic conjugated diene monomer units, carboxyl-containing monomer units, (meth)acrylate monomer units, etc.

[0104] In addition, the particulate polymer may optionally further include monomer units other than aromatic vinyl monomer units, aliphatic conjugated diene monomer units, carboxyl-containing monomer units and (meth)acrylate monomer units (hereinafter, sometimes referred to as "other monomer units").

[0105] In this specification, the term "comprising monomer units" for particulate polymers means "containing structural units derived from the monomer in a polymer obtained using the monomer".

[0106] In this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0107] -Aromatic vinyl monomer units-

[0108] Examples of aromatic vinyl monomers capable of forming aromatic vinyl monomer units include styrene, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene. Styrene is preferred. These can be used alone or in combination of two or more, but using one alone is preferred.

[0109] The proportion of aromatic vinyl monomer units in the particulate polymer is preferably 5% by mass or more, more preferably 15% by mass or more, further preferably 20% by mass or more, preferably 60% by mass or less, more preferably 55% by mass or less, further preferably 50% by mass or less, and even more preferably 35% by mass or less, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0110] Furthermore, the proportion of aromatic vinyl monomer units in the particulate polymer is preferably 5% or more and 60% or less when all repeating units (all monomer units) in the particulate polymer are 100% by mass, more preferably 15% or more and 55% or less by mass, further preferably 20% or more and 50% or less by mass, and even more preferably 20% or more and 35% or less by mass.

[0111] If the proportion of aromatic vinyl monomer units in the particulate polymer is above the lower limit mentioned above, the stability of the obtained slurry composition can be further improved.

[0112] On the other hand, if the proportion of aromatic vinyl monomer units in the particulate polymer is below the above-mentioned upper limit, the peel strength of the obtained electrode and the peel strength during high-speed coating can be improved.

[0113] In this specification, the content ratio of monomer units in the particulate polymer can be used 1 The measurements were performed using nuclear magnetic resonance (NMR) methods such as H-NMR.

[0114] -Aliphatic conjugated diene monomer unit-

[0115] Examples of aliphatic conjugated diene monomers capable of forming aliphatic conjugated diene monomer units include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, which are aliphatic conjugated diene compounds with 4 or more carbon atoms. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred, from the perspective of maintaining the tackiness of the binder composition well and improving the moisture resistance of the obtained electrode. These can be used alone or in combination of two or more.

[0116] The proportion of aliphatic conjugated diene monomer units in the particulate polymer is preferably 20% by mass or more, more preferably 25% by mass or more, further preferably 30% by mass or more, even more preferably 60% by mass or more, preferably 90% by mass or less, and more preferably 80% by mass or less, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0117] Furthermore, the proportion of aliphatic conjugated diene monomer units in the particulate polymer is preferably 20% or more and 90% or less, more preferably 25% or more and 80% or less, further preferably 30% or more and 80% or less, and even more preferably 60% or more and 80% or less, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0118] If the proportion of aliphatic conjugated diene monomer units in the particulate polymer is above the lower limit mentioned above, the peel strength of the obtained electrode and the peel strength during high-speed coating can be improved.

[0119] On the other hand, if the proportion of aliphatic conjugated diene monomer units in the particulate polymer is below the above-mentioned upper limit, the stability of the obtained slurry composition can be improved.

[0120] -Carboxyl-containing monomer unit-

[0121] Examples of carboxyl-containing monomers capable of forming carboxyl-containing monomer units include monocarboxylic acids and their derivatives, dicarboxylic acids and their anhydrides, and their derivatives.

[0122] Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid.

[0123] Examples of monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.

[0124] Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.

[0125] Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, as well as maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.

[0126] Examples of anhydrides that are dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.

[0127] In addition, as a carboxyl-containing monomer, acid anhydrides that generate carboxyl groups through hydrolysis can also be used.

[0128] The aforementioned carboxyl-containing monomers can be used alone or in combination of two or more. Moreover, among these carboxyl-containing monomers, acrylic acid and methacrylic acid are preferred from the perspective of improving the stability of the obtained slurry composition and improving the peel strength of the obtained electrode and the peel strength during high-speed coating. Methacrylic acid is more preferred.

[0129] The proportion of carboxyl-containing monomer units contained in the particulate polymer is preferably 2% by mass or more, more preferably 2.5% by mass or more, further preferably 3% by mass or more, preferably 10% by mass or less, more preferably 9% by mass or less, further preferably 5% by mass or less, and even more preferably 4% by mass or less, when the total number of repeating units (total monomer units) in the particulate polymer is 100% by mass.

[0130] Furthermore, the proportion of carboxyl-containing monomer units in the particulate polymer is preferably 2% or more and 10% or less when all repeating units (all monomer units) in the particulate polymer are 100% by mass, more preferably 2.5% or more and 9% or less by mass, further preferably 3% or more and 5% or less by mass, and even more preferably 3% or more and 4% or less by mass.

[0131] - (meth)acrylate monomer unit -

[0132] Examples of (meth)acrylate monomers capable of forming (meth)acrylate monomer units include: alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, and 2-ethylhexyl methacrylate; and hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, and 3-chloro-2-hydroxypropyl methacrylate. These can be used alone or in combination of two or more in any ratio.

[0133] The proportion of (meth)acrylate monomer units contained in the particulate polymer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, more preferably 5% by mass or less, and more preferably 2% by mass or less, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0134] -Other single-unit units-

[0135] There are no particular limitations on monomers that can form other monomer units; examples include cyanide vinyl monomers and unsaturated carboxylic acid amide monomers.

[0136] Examples of cyanide vinyl monomers include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. These can be used individually or in combination of two or more in any ratio.

[0137] Examples of unsaturated carboxylic acid amide monomers include acrylamide, methacrylamide, N-hydroxymethylacrylamide, N,N-dimethylacrylamide, etc. These can be used individually or in combination of two or more in any ratio.

[0138] The proportion of other monomer units in the particulate polymer is preferably 5% by mass or less, more preferably 1% by mass or less, and particularly preferably 0% by mass, when all repeating units (all monomer units) in the particulate polymer are 100% by mass. That is, it is particularly preferred that the particulate polymer does not contain other monomer units.

[0139] - Preferred composition of particulate polymers -

[0140] From the perspective of effectively reducing the internal resistance of the obtained secondary battery, the particulate polymer preferably contains aromatic vinyl monomer units, more preferably contains aromatic vinyl monomer units, conjugated diene monomer units and carboxyl-containing monomer units, further preferably a polymer containing styrene, 1,3-butadiene and (meth)acrylic acid or a polymer containing styrene, isoprene and (meth)acrylic acid, and even more preferably a polymer containing styrene, 1,3-butadiene and (meth)acrylic acid.

[0141] <<Structure of Particulate Polymers>>

[0142] Particulate polymers can be either granular polymers with a uniform monomer unit composition (types and proportions of monomer units) or granular polymers with a non-uniform monomer unit composition. Furthermore, granular polymers with a non-uniform monomer unit composition can be obtained, for example, through two-stage polymerization as described later.

[0143] Here, in the case of obtaining a particulate polymer with a non-uniform monomer unit composition through two-stage polymerization, the composition of the monomer units on the inner side (first stage) and the outer side (second stage) of the particulate polymer can be different.

[0144] When the composition of the inner and outer monomer units inside the particulate polymer is different, the proportion of carboxyl-containing monomer units on the inner side of the particulate polymer is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, preferably 1.5% by mass or less, and more preferably 1.2% by mass or less, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0145] Furthermore, when the composition of the inner and outer monomer units inside the particulate polymer is different, the proportion of the carboxyl-containing monomer units on the outer side of the particulate polymer is preferably 1% or more by mass, more preferably 2% or more by mass, more preferably 8% or less by mass, more preferably 5% or less by mass, and even more preferably 4% or less by mass, when all repeating units (all monomer units) in the particulate polymer are 100% by mass.

[0146] When the composition of the inner and outer monomer units inside the particulate polymer is different, from the perspective of being able to maintain the tackiness of the binder composition well, and further improve the peel strength of the obtained electrode and the peel strength during high-speed coating, thereby reducing the internal resistance of the obtained secondary battery and improving the cycle characteristics of the obtained secondary battery, the outer side of the particulate polymer preferably contains methacrylic acid monomer units.

[0147] <<Proportion of Particulate Polymers>>

[0148] The proportion of particulate polymer in the adhesive composition is preferably 20% by mass or more, more preferably 25% by mass or more, preferably 60% by mass or less, and more preferably 50% by mass or less.

[0149] <<Preparation Methods of Particulate Polymers>>

[0150] Particulate polymers can be polymerized using known polymerization methods such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization.

[0151] As a polymerization reaction, addition polymerization such as ionic polymerization, free radical polymerization, and living free radical polymerization can be used.

[0152] During polymerization reactions, commonly used additives such as molecular weight regulators, emulsifiers, dispersants, polymerization initiators, and polymerization aids can be used. The amounts of these additives used can be the amounts typically employed.

[0153] There are no particular limitations on the preparation of particulate polymers; for example, it can be carried out according to the following steps.

[0154] First, the monomers described above are mixed with water, an emulsifier, and a polymerization initiator. The mixture (emulsion) is then heated to initiate a polymerization reaction. When the specified polymerization conversion rate is reached, the reaction is stopped by cooling, yielding a mixture containing particulate polymer. Unreacted monomers are removed from the mixture. The pH of the mixture is then adjusted appropriately to obtain an aqueous dispersion of the particulate polymer.

[0155] In the preparation of particulate polymers, when using aromatic vinyl monomers, aliphatic conjugated diene monomers, and carboxyl-containing monomers, a portion of the carboxyl-containing monomers can be added in stages. For example, all the aromatic vinyl monomers, aliphatic conjugated diene monomers, and a portion of the carboxyl-containing monomers can be added first to carry out the polymerization reaction. Then, the remaining carboxyl-containing monomers can be added continuously over a specified time to carry out the polymerization reaction (two-stage polymerization).

[0156] Furthermore, in the preparation of particulate polymers, when using aromatic vinyl monomers, aliphatic conjugated diene monomers, carboxyl-containing monomers, and (meth)acrylate monomers, for example, the entire amount of aliphatic conjugated diene monomers, along with a portion of the aromatic vinyl monomers and carboxyl-containing monomers, can be added first to carry out a polymerization reaction. Then, the (meth)acrylate monomers, along with the remaining aromatic vinyl monomers and carboxyl-containing monomers, can be added continuously over a specified time to carry out a polymerization reaction (two-stage polymerization).

[0157] Solvent

[0158] Examples of solvents that can be included in the adhesive composition of the present invention include, for example, water and water-soluble organic solvents. Among these, water is preferred. These solvents can be used alone or in combination of two or more.

[0159] Here, the proportion of water in the solvent is preferably 90% or more when the total solvent is 100% by mass.

[0160] <Other Ingredients>

[0161] The adhesive composition of the present invention may also contain other components without prejudice to the purpose of the invention. Examples of such other components include, for instance, antioxidants, defoamers, dispersants, pH adjusters, etc.

[0162] Other ingredients may be used alone or in combination of two or more in any ratio.

[0163] <Preparation Method of Adhesive Composition for Non-Aqueous Secondary Battery Electrodes>

[0164] The adhesive composition of the present invention is not particularly limited, and can be prepared by mixing particulate polymers with other freely usable components in the presence of a solvent. Furthermore, when preparing the adhesive composition using an aqueous dispersion of particulate polymers, the liquid components contained in the aqueous dispersion can be used directly as a solvent for the adhesive composition.

[0165] (Slurry composition for non-aqueous secondary battery electrodes)

[0166] The slurry composition of the present invention is a composition used for forming an electrode composite material layer of an electrode, comprising the above-described binder composition and an electrode active substance. That is, the slurry composition of the present invention contains the above-described particulate polymer and electrode active substance, and may optionally contain solvents and other components. Furthermore, because the slurry composition of the present invention contains the above-described binder composition, it can impart excellent peel strength to the electrode.

[0167] <Adhesive Composition>

[0168] As an adhesive composition, the adhesive composition of the present invention described above comprises a particulate polymer and may also optionally contain solvents and other components.

[0169] Furthermore, there is no particular limitation on the amount of binder composition in the slurry composition. For example, the amount of binder composition can be set to be 0.5 parts by mass and 15 parts by mass or less relative to 100 parts by mass of the electrode active material in terms of solid components.

[0170] <Electrode Active Materials>

[0171] There are no particular limitations on the electrode active material, and known electrode active materials used in secondary batteries can be used. Specifically, for example, as an electrode active material that can be used in the electrode composite material layer of a lithium-ion secondary battery, which is an example of a secondary battery, there are no particular limitations, and the following electrode active materials can be used.

[0172] <<Positive Electrode Active Materials>>

[0173] As the positive electrode active material incorporated in the positive electrode composite layer of the positive electrode in a lithium-ion secondary battery, compounds containing transition metals, such as transition metal oxides, transition metal sulfides, and composite metal oxides of lithium and transition metals, can be used. Examples of transition metals include Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo.

[0174] Specifically, as a positive electrode active material, there are no particular limitations, but examples include lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium-containing composite oxides of Co-Ni-Mn, lithium-containing composite oxides of Ni-Mn-Al, lithium-containing composite oxides of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), and other materials composed of Li... 1+x Mn 2-x O4 (0 < X ​​< 2) represents lithium-excess spinel compounds, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O2, LiNi 0.5 Mn 1.5 O4, etc.

[0175] In addition, the above-mentioned positive electrode active materials can be used alone or in combination of two or more.

[0176] <<Negative Electrode Active Materials>>

[0177] Examples of negative electrode active materials used in the negative electrode composite material layer of a lithium-ion secondary battery include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials that combine these materials.

[0178] Here, carbon-based anode active materials refer to active materials with a carbon-based backbone that can be intercalated (also called "doped") with lithium. Specifically, examples of carbon-based anode active materials include: coke, mesophase carbon microspheres (MCMB), mesophase pitch-based carbon fibers, pyrolysis vapor-grown carbon fibers, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), and hard carbon; as well as graphitic materials such as natural graphite and artificial graphite.

[0179] Furthermore, metal-based anode active materials refer to active materials containing metals, typically those containing elements capable of intercalating lithium in their structure, and with a theoretical capacity of 500 mAh / g or more per unit mass when lithium is intercalated. Examples of metal-based active materials include lithium metal, elemental metals capable of forming lithium alloys (e.g., Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.), and their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. Furthermore, oxides such as lithium titanate can be cited.

[0180] In addition, the above-mentioned negative electrode active materials can be used alone or in combination of two or more.

[0181] Solvent

[0182] As a solvent that can be included in the slurry composition, the same solvents listed in the above-mentioned "Binder Composition for Non-Aqueous Secondary Battery Electrodes" can be used.

[0183] <Other Ingredients>

[0184] Other components that can be incorporated into the slurry composition are not particularly limited, and examples include thickeners, conductive materials, and other components that are the same as those that can be incorporated into the binder composition of the present invention.

[0185] In addition, other ingredients can be used alone or in combination of two or more in any ratio.

[0186] <Preparation of Slurry Compositions for Non-Aqueous Secondary Battery Electrodes>

[0187] There are no particular limitations on the preparation method of the slurry composition.

[0188] For example, a slurry composition can be prepared by mixing a binder composition, an electrode active material, and other components to be used as needed in the presence of a solvent.

[0189] Furthermore, the solvent used in preparing the slurry composition also includes the solvent contained in the binder composition. In addition, there are no particular limitations on the mixing method; mixing can be performed using commonly used mixers and dispersers.

[0190] (Electrodes for non-aqueous secondary batteries)

[0191] The electrode for a non-aqueous secondary battery of the present invention comprises an electrode composite material layer formed using the aforementioned slurry composition for a non-aqueous secondary battery electrode. Therefore, the electrode composite material layer is formed from the dried product of the aforementioned slurry composition and typically contains an electrode active material and components derived from particulate polymers, and optionally contains other components. Furthermore, each component contained in the electrode composite material layer is the same as that contained in the aforementioned slurry composition for a non-aqueous secondary battery electrode, and the preferred proportions of these components are the same as the preferred proportions of the components in the slurry composition. In addition, while the particulate polymer exists in a particulate form in the slurry composition, it can be in a particulate form or any other arbitrary shape in the electrode composite material layer formed using the slurry composition.

[0192] Furthermore, the electrode for non-aqueous secondary batteries of the present invention exhibits excellent peel strength because it uses the above-mentioned slurry composition for non-aqueous secondary battery electrodes to form an electrode composite material layer.

[0193] Manufacturing of electrodes for non-aqueous secondary batteries

[0194] Here, the electrode composite material layer of the electrode for the non-aqueous secondary battery of the present invention can be formed, for example, by the following method.

[0195] 1) A method of coating the slurry composition of the present invention onto the surface of a current collector and then drying it;

[0196] 2) A method for drying a current collector after impregnating it with the slurry composition of the present invention; and

[0197] 3) A method of coating the slurry composition of the present invention onto a release substrate, drying it to produce an electrode composite material layer, and transferring the obtained electrode composite material layer onto the surface of a current collector.

[0198] Of these, the method described in 1) above is particularly preferred because it is easy to control the thickness of the electrode composite layer. The method described in 1) above specifically includes: a step of coating a slurry composition onto a current collector (coating step); and a step of drying the slurry composition coated onto the current collector to form an electrode composite layer on the current collector (drying step).

[0199] <<Coating Process>>

[0200] There are no particular limitations on the method for coating the above-mentioned slurry composition onto the current collector, and any known method can be used. Specifically, as coating methods, blade coating, dip coating, reverse roller coating, direct roller coating, gravure printing, extrusion coating, brush coating, etc., can be used. In this case, the slurry composition can be coated only on one side of the current collector, or it can be coated on both sides. The thickness of the slurry film on the current collector before drying can be appropriately set according to the thickness of the electrode composite material layer obtained after drying.

[0201] Here, a material with conductivity and electrochemical durability is used as the current collector for the coating slurry composition. Specifically, current collectors made of materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum can be used. Furthermore, one of the above materials can be used alone, or two or more can be used in any ratio.

[0202] <<Drying Process>>

[0203] The method for drying the slurry composition on the current collector is not particularly limited, and known methods can be used, such as drying methods using warm air, hot air, or low-humidity air; vacuum drying methods; and drying methods using irradiation with infrared rays, electron beams, etc. By drying the slurry composition on the current collector in this way, an electrode composite material layer can be formed on the current collector, resulting in an electrode for a non-aqueous secondary battery having both a current collector and an electrode composite material layer.

[0204] Alternatively, after the drying process, the electrode composite layer can be pressurized using metal molds or rollers. Pressurization improves the adhesion between the electrode composite layer and the current collector, and also increases the density of the resulting electrode composite layer. Furthermore, if the electrode composite layer contains a curable polymer, it is preferable to cure the polymer after the electrode composite layer is formed.

[0205] (Non-aqueous secondary battery)

[0206] The non-aqueous secondary battery of the present invention includes a positive electrode, a negative electrode, an electrolyte, and a spacer, and uses the aforementioned non-aqueous secondary battery electrode as at least one of the positive and negative electrodes. Furthermore, because the non-aqueous secondary battery of the present invention is manufactured using the aforementioned non-aqueous secondary battery electrode as at least one of the positive and negative electrodes, it exhibits excellent performance.

[0207] Furthermore, the following description will focus on the case where the secondary battery is a lithium-ion secondary battery, but the present invention is not limited to this example.

[0208] <Electrode>

[0209] There are no particular limitations on the electrodes that can be used in the non-aqueous secondary battery of the present invention, other than the electrodes for the non-aqueous secondary battery of the present invention described above. Known electrodes used in the manufacture of secondary batteries can be used. Specifically, electrodes other than the electrodes for the non-aqueous secondary battery of the present invention described above can be used, such as electrodes formed by forming an electrode composite material layer on a current collector using known manufacturing methods.

[0210] Electrolyte

[0211] As an electrolyte, an organic electrolyte in which the supporting electrolyte is dissolved in an organic solvent is typically used. For example, lithium salts can be used as the supporting electrolyte for lithium-ion secondary batteries. Examples of lithium salts include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, and (C2F5SO2)NLi. Among these, LiPF6, LiClO4, and CF3SO3Li are preferred due to their high solubility in solvents and high degree of dissociation. Furthermore, a single electrolyte can be used, or two or more can be used in any ratio. Generally, there is a tendency for higher dissociation degrees of supporting electrolytes to result in higher lithium-ion conductivity; therefore, the lithium-ion conductivity can be adjusted by the type of supporting electrolyte.

[0212] As for the organic solvent used in the electrolyte, there are no particular limitations as long as it can dissolve the supporting electrolyte. Preferred solvents include: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butyl carbonate (BC), methyl ethyl carbonate (EMC), and vinylene carbonate (VC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; and sulfur-containing compounds such as sulfolane and dimethyl sulfoxide. Mixtures of these solvents can also be used. Among these, carbonates are preferred due to their high dielectric constant and wide stable potential range. Generally, the lower the viscosity of the solvent used, the higher the lithium-ion conductivity; therefore, the lithium-ion conductivity can be adjusted by the type of solvent.

[0213] Furthermore, the electrolyte concentration in the electrolyte can be appropriately adjusted. Additionally, known additives can be added to the electrolyte.

[0214] <spacer>

[0215] There are no particular limitations on the spacer; for example, the spacer described in Japanese Patent Application Publication No. 2012-204303 can be used. Among these, a microporous membrane made of polyolefin-based (polyethylene, polypropylene, polybutene, polyvinyl chloride) resin is preferred from the perspective that the overall film thickness of the spacer can be reduced, thereby increasing the proportion of electrode active material in the secondary battery and thus increasing the capacity per unit volume.

[0216] Furthermore, the secondary battery of the present invention can be manufactured, for example, by overlapping the positive and negative electrodes with a spacer between them, and then, as needed, winding, folding, or placing them into a battery container according to the battery shape, injecting electrolyte into the battery container, and sealing it. Here, in the non-aqueous secondary battery of the present invention, the aforementioned non-aqueous secondary battery electrode is used as at least one of the positive and negative electrodes, preferably as the negative electrode. Additionally, in the non-aqueous secondary battery of the present invention, to prevent internal pressure rise, overcharging, and over-discharging, overcurrent protection components such as fuses and PTC elements, porous metal mesh, and conductive plates can be provided as needed. The shape of the secondary battery can be any of, for example, coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.

[0217] Example

[0218] The present invention will now be described in detail based on embodiments, but the present invention is not limited to these embodiments. Furthermore, in the following description, unless otherwise specified, "%" and "parts" refer to quantities based on mass.

[0219] Furthermore, in the examples and comparative examples, the transverse relaxation time T of the particulate polymer was... 2ATransverse relaxation time T of particulate polymers 2B The percentage of THF-insoluble components in the particulate polymer, the volume average particle size of the particulate polymer, the peel strength of the electrode (negative electrode), the peel strength of the electrode (negative electrode) during high-speed coating, the viscosity of the binder composition, the internal resistance of the lithium-ion secondary battery, and the cycle characteristics of the lithium-ion secondary battery are determined or evaluated according to the following methods.

[0220] <Transverse relaxation time T of particulate polymers 2A >

[0221] <<Pulse NMR Measurement>>

[0222] The aqueous dispersions (binder compositions) of the particulate polymers obtained in the examples and comparative examples were adjusted to a solids concentration of 29.0% by mass or more and 31.0% by mass or less, and a pH of 3.0 or more and 4.5 or less. The adjusted binder composition was then introduced into a 10 mm diameter glass sample tube (manufactured by Bruker, model 1824511, 10 mm in diameter, 180 mm in length, flat bottom). The sample tube was placed in a pulsed NMR apparatus (Bruker mq20) and analyzed by CPMG (Carr-Purcell-Meiboom-Gill method) at 30°C under the following conditions to obtain... 1 The free induction decay curve of H's transverse relaxation.

[0223] -Conditions for CPMG method-

[0224] · 1 H-resonance frequency: 20MHz;

[0225] • Total number of times: 64;

[0226] • Repeat time: 2 seconds;

[0227] • Number of measurement points: 1000.

[0228] <<Calculation of Lateral Relaxation Time T2>>

[0229] The transverse relaxation time T2 was obtained by fitting the free induction decay curve y(t) obtained above with an exponential function. Additionally, the analysis software "TDNMR-A" manufactured by Bruker was used, and the function was fitted with an exponential function according to the product manual. Furthermore, the fitting was performed using the following equation (2).

[0230]

[0231] In equation (2), A represents the signal intensity at t=0, T2 represents the transverse relaxation time, and t represents time. Using the CPMG method described above, the transverse relaxation time T2 was measured three times, and the average value was calculated. This average value was taken as the transverse relaxation time T for pH values ​​above 3.0 and below 4.5. 2A .

[0232] <Transverse relaxation time T of particulate polymers 2B >

[0233] The pH of the aqueous dispersion (binder composition) of the particulate polymer obtained in the examples and comparative examples was adjusted to 6.5 or higher and 8.0 or lower. Otherwise, the "transverse relaxation time T of the particulate polymer" was adjusted accordingly. 2A Similarly, calculate the average value of the transverse relaxation time T2, and use this average value as the transverse relaxation time T. 2B .

[0234] <Volume average particle size of particulate polymers>

[0235] Using a particle size distribution measuring device (manufactured by Shimadzu Corporation, product name "SALD-2300") based on the principle of laser diffraction scattering, the particle size distribution of the obtained binder composition (aqueous dispersion of particulate polymer, with solid component concentration adjusted to 0.1% by mass) was measured according to JIS Z 8825. In the measured particle size distribution, the particle size at which the cumulative volume reaches 50% (D50) calculated from the smallest particle size side was taken as the volume average particle size.

[0236] <Percentage of THF-insoluble components in particulate polymers>

[0237] The aqueous dispersions (binder compositions) of the particulate polymers obtained in the examples and comparative examples were dried at 50% humidity and 23–25°C to form a film with a thickness of 1 ± 0.3 mm. The film was dried in a vacuum dryer at 60°C for 10 hours. Afterward, the dried film was cut into 3–5 mm squares and weighed precisely about 1 g. The mass of the film obtained by cutting was set as w0. The film was immersed in 50 g of tetrahydrofuran (THF) for 24 hours. Afterward, the film removed from the THF was vacuum dried at 105°C for 3 hours, and the mass w1 of the insoluble component was measured. Then, the THF insoluble component percentage was calculated using the following formula (3).

[0238]

[0239] <Peel strength of electrode (negative electrode)>

[0240] The negative electrode prepared in the examples and comparative examples was cut into rectangles with a length of 100 mm and a width of 10 mm to serve as test pieces. With the surface of the negative electrode composite layer facing down, transparent tape was adhered to the surface of the negative electrode composite layer. The transparent tape specified in JIS Z1522 was used. The transparent tape was then fixed to the test bench. The stress was then measured when one end of the current collector was stretched vertically upwards at a tensile speed of 50 mm / min and peeled off. This measurement was performed three times, and the average value was calculated. This average value was used as the peel strength and evaluated according to the following criteria.

[0241] A: Peel strength is above 13 N / m;

[0242] B: Peel strength is above 10 N / m and less than 13 N / m;

[0243] C: Peel strength is above 7 N / m and less than 10 N / m;

[0244] D: Peel strength is less than 7 N / m.

[0245] <Peel strength of electrode (negative electrode) during high-speed coating>

[0246] In the examples and comparative examples, the negative electrode slurry composition was coated using a comma coating machine at a speed of 3.6 m / min, with a dried weight per unit area of ​​10.5 mg / cm³. 2 The negative electrode is coated onto a 15μm thick copper foil, which serves as the current collector. The copper foil coated with the negative electrode slurry composition is then dried in an oven at 120°C for 20 seconds and in an oven at 150°C for 20 seconds to obtain the negative electrode (the negative electrode during high-speed coating).

[0247] Using the obtained high-speed coated negative electrode, the peel strength of the electrode (negative electrode) during high-speed coating was measured in the same manner as the above-mentioned "peel strength of electrode (negative electrode)," and evaluated according to the following criteria.

[0248] A: The peel strength during high-speed coating is above 11 N / m;

[0249] B: The peel strength during high-speed coating is above 8 N / m and less than 11 N / m;

[0250] C: The peel strength during high-speed coating is above 5 N / m and less than 8 N / m;

[0251] D: The peel strength during high-speed coating is less than 5 N / m.

[0252] <Adhesive properties of the adhesive composition>

[0253] After adjusting the solid content concentration of the adhesive compositions obtained in the examples and comparative examples to 30% by mass, the viscosity of the adhesive compositions was measured using a Type B viscometer (manufactured by Toki Sangyo Co., Ltd., product name "TVB-10", speed: 60 rpm), and evaluated according to the following criteria. The temperature during viscosity measurement was 25°C. Furthermore, if the viscosity of the adhesive composition is 10 mPa·s or more and 3000 mPa·s or less, it can be said that the adhesive composition has good adhesion.

[0254] A: Above 10 mPa·s and below 1500 mPa·s;

[0255] B: Greater than 1500 mPa·s and less than 3000 mPa·s;

[0256] C: less than 10 mPa·s or greater than 3000 mPa·s.

[0257] <Internal resistance of lithium-ion secondary batteries>

[0258] To evaluate the internal resistance of a lithium-ion secondary battery, the IV resistance was measured as follows. The following conditioning process was performed: at 25°C, the battery was charged at a rate of 0.1C to a voltage of 4.2V. After a 10-minute rest, it was discharged at a constant current (CC) of 0.1C to 3.0V. This process was repeated three times. Then, at -10°C, the battery was charged at 1C (C is a value expressed as rated capacity (mA) / 1 hour (h)) to 3.75V. Around 3.75V, the battery was charged and discharged for 20 seconds at rates of 0.5C, 1.0C, 1.5C, and 2.0C, respectively. For each case, the battery voltage on the charging side after 15 seconds was plotted against the current value, and the slope was used as the IV resistance (Ω). The obtained IV resistance value (Ω) was compared with the IV resistance of Example 4, and evaluated using the following criteria. Furthermore, a smaller IV resistance value indicates a lower internal resistance of the secondary battery.

[0259] A: Less than 85% compared to the IV resistance of Example 4;

[0260] B: Compared to the IV resistance of Example 4, it is 85% or more and less than 95%;

[0261] C: Compared to the IV resistance of Example 4, it is 95% or more and less than 105%;

[0262] D: The resistance of IV is 105% or more compared to that of Example 4.

[0263] <Cycle Characteristics of Lithium-ion Secondary Batteries>

[0264] The lithium-ion secondary batteries prepared in the examples and comparative examples were left to stand at 25°C for 5 hours after electrolyte injection. Next, they were charged at 0.2C at 25°C to a cell voltage of 3.65V, followed by an aging treatment at 60°C for 12 hours. Then, they were discharged at 0.2C at 25°C to a cell voltage of 3.00V. Afterward, they were charged at 0.2C using a constant current (CC)-constant voltage (CV) method (upper limit cell voltage 4.20V), and discharged at 0.2C using a CC method to 3.00V. This charge-discharge cycle at 0.2C was repeated three times.

[0265] Subsequently, at a temperature of 25°C, 100 charge-discharge cycles were performed with a battery cell voltage of 4.20-3.00V and a charge-discharge rate of 1.0C. The discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 200th cycle was defined as X2.

[0266] Using the discharge capacities X1 and X2, calculate the capacity change rate expressed as ΔC' = (X2 / X1) × 100 (%), and evaluate it using the following benchmarks. The larger the value of this capacity change rate ΔC', the better the cycle performance.

[0267] A: ΔC' is above 93%;

[0268] B: ΔC' is above 90% and less than 93%;

[0269] C: ΔC' is above 87% and less than 90%;

[0270] D: ΔC' is less than 87%.

[0271] (Example 1)

[0272] Preparation of Aqueous Dispersions of Particulate Polymers (Binder Compositions for Non-Aqueous Secondary Battery Anodes)

[0273] First, in the first stage of polymerization, 24 parts of styrene as an aromatic vinyl monomer, 72 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 1 part of methacrylic acid as a carboxyl-containing monomer, 0.6 parts of alkyl diphenyl ether disulfonate as an emulsifier, 143 parts of deionized water, 0.1 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.3 parts of potassium persulfate as a polymerization initiator were added to a 5MPa pressure vessel equipped with a stirrer. After thorough stirring, the mixture was heated to 55°C to initiate polymerization and reacted for 10 hours. Then, the mixture was heated to 65°C and reacted for another 6 hours.

[0274] Next, in the second stage of polymerization, in the same pressure vessel, 3 parts of methacrylic acid, a carboxyl-containing monomer, were added at a rate of 1 part / min under stirring, heated to 85°C, and reacted for 6 hours. Afterwards, unreacted monomers were removed by heated vacuum distillation to obtain an aqueous dispersion of the particulate polymer as a binder composition.

[0275] Using the obtained binder composition, the transverse relaxation time T of the particulate polymer was determined or evaluated. 2A Transverse relaxation time T of particulate polymers 2B The percentage of THF-insoluble components in the particulate polymer, the volume average particle size of the particulate polymer, and the viscosity of the binder composition were measured. The results are shown in Table 1.

[0276] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 7.0.

[0277] <Preparation of Slurry Composition for Anode of Non-Aqueous Secondary Batteries>

[0278] Add 100 parts of artificial graphite (tap density: 0.85 g / cm³) as the negative electrode active material to a planetary mixer equipped with a disperser. 3 A mixture was prepared by mixing 1 part of carbon black (manufactured by TIMCAL Corporation, product name "Super C65") as a conductive material and 1.2 parts of carboxymethyl cellulose (manufactured by Daicel Corporation, product name "Daicel2200") as a thickener, based on the solid content. The mixture was adjusted to a solid content concentration of 60% with deionized water and then mixed at 25°C for 60 minutes. Next, the solid content concentration was adjusted to 52% with deionized water and further mixed at 25°C for 15 minutes to obtain a liquid mixture. To the liquid mixture, 2.0 parts of the binder composition prepared above, based on the solid content, and deionized water were added, adjusting the final solid content concentration to 48%. After further mixing for 10 minutes, degassing was performed under reduced pressure to obtain a slurry composition for a negative electrode with good flowability.

[0279] The peel strength of the electrode (negative electrode) during high-speed coating was evaluated using the obtained negative electrode slurry composition.

[0280] <Formation of the negative electrode>

[0281] The obtained negative electrode slurry composition was coated using a comma coater at a speed of 1.2 m / min, with a dried weight per unit area of ​​10.5 mg / cm³. 2 The coating was applied to a 15 μm thick copper foil, which served as the current collector, and then dried. This drying was performed by conveying the copper foil at a speed of 1.2 m / min in an oven at 120°C for 1 minute, followed by a conveying process at 130°C for 1 minute. The resulting negative electrode raw material was then calendered using a roll press to obtain a negative electrode composite layer with a density of 1.70 g / cm³. 3 The negative electrode.

[0282] The peel strength of the electrode (negative electrode) was evaluated using the obtained negative electrode. The results are shown in Table 1.

[0283] <Formation of the Positive Electrode>

[0284] 100 parts of LiCoO2 with a median particle size of 12 μm as the positive electrode active material, 2 parts of acetylene black (manufactured by Denki Kagaku Kogyo Co., Ltd., product name "HS-100") as the conductive material, 2 parts of polyvinylidene fluoride (manufactured by Kureha Co., Ltd., product name "#7208") as the binder (based on solids content), and N-methylpyrrolidone as the solvent were mixed to bring the total solids content to 70%. These were then mixed using a planetary mixer to obtain a slurry composition for the positive electrode.

[0285] The obtained positive electrode slurry composition was coated using a comma coating machine to achieve a dry weight of 23 mg / cm³. 2 The material was coated onto a 20 μm thick aluminum foil, which served as the current collector, and then dried. This drying was performed by conveying the aluminum foil at 0.5 m / min in an oven at 60°C for 2 minutes. Afterward, it was heat-treated at 120°C for 2 minutes to obtain the positive electrode raw material. The positive electrode raw material was then calendered using a roll press to obtain a positive electrode composite layer with a density of 4.0 g / cm³. 3 The positive pole.

[0286] <Preparation of spacers>

[0287] As the spacer made of spacer substrate, a single-layer polypropylene spacer (manufactured by Celgard Corporation, product name "Celgard 2500") was prepared. Alternatively, this polypropylene spacer is a 25 μm thick polypropylene microporous membrane.

[0288] <Making of Lithium-ion Secondary Batteries>

[0289] A laminate is obtained by placing the pressed positive electrode, pressed negative electrode, and spacer between the positive and negative electrodes in a spacer / positive electrode / spacer / negative electrode configuration. Next, the laminate of electrodes and spacers is wound onto a core with a diameter of 20 mm to obtain a wound body having a positive electrode, spacer, and negative electrode. Then, the wound body is compressed unidirectionally at a speed of 10 mm / s to a thickness of 4.5 mm to obtain a flat body. Furthermore, the obtained flat body is elliptical when viewed from above, with a major axis to minor axis ratio (major axis / minor axis) of 7.7.

[0290] In addition, a non-aqueous electrolyte was prepared (a 1.0 M LiPF6 solution, in a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (mass ratio), with 2 volumes of ethylene carbonate (VC) added as an additive).

[0291] Next, the aforementioned flat body and the aforementioned non-aqueous electrolyte were housed together in an aluminum laminated casing. Then, after connecting the negative and positive electrode leads to the designated positions, the opening of the laminated casing was sealed by heat, thus manufacturing a laminated lithium-ion secondary battery as a non-aqueous secondary battery. Furthermore, the resulting secondary battery is a pouch-shaped battery with a width of 35mm × height of 48mm × thickness of 5mm and a nominal capacity of 700mAh.

[0292] The obtained lithium-ion secondary batteries were used to evaluate the internal resistance and cycle characteristics of the lithium-ion secondary batteries. The results are shown in Table 1.

[0293] (Example 2)

[0294] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of 1,3-butadiene used in the first stage was changed from 72 parts to 70 parts, and the amount of methacrylic acid used in the second stage was changed from 3 parts to 5 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0295] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 3.8. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 6.6.

[0296] (Example 3)

[0297] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of 1,3-butadiene used in the first stage was changed from 72 parts to 74 parts, and the amount of methacrylic acid used in the second stage was changed from 3 parts to 1 part. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0298] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 4.3. The transverse relaxation time T of the particulate polymer was... 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 7.6.

[0299] (Example 4)

[0300] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of 1,3-butadiene used in the first stage was changed from 72 parts to 67 parts, and the amount of methacrylic acid used in the second stage was changed from 3 parts to 8 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0301] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 3.4. The transverse relaxation time T of the particulate polymer was... 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 29.8% by mass and a pH of 6.5.

[0302] (Example 5)

[0303] As the adhesive composition, the adhesive composition obtained by the preparation method shown below was used, except that various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0304] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.1. The transverse relaxation time T of the particulate polymer was... 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 7.1.

[0305] Preparation of Aqueous Dispersions of Particulate Polymers (Binder Compositions for Non-Aqueous Secondary Battery Anodes)

[0306] First, in the first stage of polymerization, 21 parts of styrene as an aromatic vinyl monomer, 72 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 1 part of methacrylic acid as a carboxyl-containing monomer, 0.6 parts of alkyl diphenyl ether disulfonate as an emulsifier, 143 parts of deionized water, 0.1 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.3 parts of potassium persulfate as a polymerization initiator were added to a 5MPa pressure vessel equipped with a stirrer. After thorough stirring, the mixture was heated to 55°C to begin polymerization and reacted for 10 hours. Then, the mixture was heated to 65°C and reacted for another 6 hours.

[0307] Next, in the second stage of polymerization, in the same pressure vessel, under stirring, 2 parts of styrene as an aromatic vinyl monomer, 1 part of methacrylate as a (meth)acrylate monomer, and 3 parts of methacrylic acid as a carboxyl-containing monomer were added at a rate of 1 part / min. The mixture was heated to 85°C and reacted for 6 hours. Afterward, unreacted monomers were removed by heated vacuum distillation to obtain an aqueous dispersion of the particulate polymer as a binder composition.

[0308] (Example 6)

[0309] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of styrene used in the first stage was changed from 24 parts to 40 parts, and the amount of 1,3-butadiene was changed from 72 parts to 56 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0310] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.2% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 7.1.

[0311] (Example 7)

[0312] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of styrene used in the first stage was changed from 24 parts to 15 parts, and the amount of 1,3-butadiene was changed from 72 parts to 81 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0313] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 6.9.

[0314] (Example 8)

[0315] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), 72 parts of 1,3-butadiene in the first stage were replaced with 72 parts of isoprene. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0316] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 6.7.

[0317] (Example 9)

[0318] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of styrene used in the first stage was changed from 24 parts to 64 parts, and the amount of 1,3-butadiene was changed from 72 parts to 32 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0319] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 7.2.

[0320] (Example 10)

[0321] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of styrene used in the first stage was changed from 24 parts to 4 parts, and the amount of 1,3-butadiene was changed from 72 parts to 92 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0322] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 3.9. The transverse relaxation time T of the particulate polymer was... 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 6.9.

[0323] (Example 11)

[0324] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the 3 parts of methacrylic acid in the second stage were replaced with 3 parts of acrylic acid. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0325] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solids concentration of 30.1% by mass and a pH of 3.9. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 7.0.

[0326] (Comparative Example 1)

[0327] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), the amount of 1,3-butadiene used in the first stage was changed from 72 parts to 74.5 parts, and the amount of methacrylic acid used in the second stage was changed from 3 parts to 0.5 parts. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0328] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.2. The transverse relaxation time T of the particulate polymer was... 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.1% by mass and a pH of 7.8.

[0329] (Comparative Example 2)

[0330] In the preparation of the aqueous dispersion of the particulate polymer (a binder composition for the negative electrode of a non-aqueous secondary battery), 3 parts of methacrylic acid in the second stage were replaced with 3 parts of itaconic acid. Otherwise, all operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0331] In addition, the transverse relaxation time T of the particulate polymer 2A In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 4.0. The transverse relaxation time T of the particulate polymer was determined. 2B In the determination, the aqueous dispersion of the particulate polymer (binder composition) was adjusted to a solid component concentration of 30.0% by mass and a pH of 7.8.

[0332] Additionally, in Table 1,

[0333] "St" represents styrene.

[0334] “BD” represents 1,3-butadiene.

[0335] "IP" stands for isoprene.

[0336] "MAA" stands for methacrylic acid.

[0337] "AA" indicates acrylic acid.

[0338] "IA" represents itaconic acid.

[0339] "MMA" stands for methyl methacrylate.

[0340] “T 2A "T" represents the lateral relaxation time. 2A ,

[0341] “T 2B "T" represents the lateral relaxation time. 2B .

[0342] [Table 1]

[0343]

[0344] As can be clearly seen from Table 1, the adhesive compositions of Examples 1 to 11 can impart excellent peel strength to the electrodes.

[0345] Industrial availability

[0346] According to the present invention, it is possible to provide an adhesive composition for a non-aqueous secondary battery electrode that can impart excellent peel strength to the electrode for a non-aqueous secondary battery.

[0347] Furthermore, according to the present invention, a slurry composition for a non-aqueous secondary battery electrode can be provided, which can impart excellent peel strength to the electrode for a non-aqueous secondary battery.

[0348] Furthermore, according to the present invention, an electrode for a non-aqueous secondary battery with excellent peel strength can be provided.

[0349] Furthermore, according to the present invention, a non-aqueous secondary battery having electrodes for a non-aqueous secondary battery with excellent performance can be provided.

Claims

1. A binder composition for a non-aqueous secondary battery electrode, comprising a particulate polymer, The transverse relaxation time T was obtained by pulse NMR CPMG determination of the particulate polymer at one point within the pH range of above 3.0 and below 4.

5. 2A The transverse relaxation time T obtained by CPMG method with pulsed NMR at a single point in the pH range above 6.5 and below 8.0 is compared with that obtained by the same method. 2B At least one combination of them satisfies the following relationship (1): 。 2. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The transverse relaxation time T 2B It is between 10 msec and 1500 msec.

3. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The particulate polymer contains aromatic vinyl monomer units.

4. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The volume average particle size of the particulate polymer is greater than 100 nm and less than 300 nm.

5. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The insoluble component of the particulate polymer in tetrahydrofuran is more than 70% by mass.

6. A slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material and a binder composition for a non-aqueous secondary battery electrode according to any one of claims 1 to 5.

7. An electrode for a non-aqueous secondary battery, having an electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery electrode as described in claim 6.

8. A non-aqueous secondary battery, comprising a positive electrode, a negative electrode, a spacer, and an electrolyte. At least one of the positive electrode and the negative electrode is the electrode for a non-aqueous secondary battery as described in claim 7.

Citation Information

Patent Citations

  • Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery

    JP2012204303A

  • Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery

    WO2023008582A1